Dialecticisms as a Means of Expressiveness of Myroslav Dochynez’ Texts (Linguostylistic Studies, 2015)
The article analyzes how as a result of linguocide and ethnocide policy the dialect area was destroyed and passive stock got a number of lexemes. That is why the study of dialect vocabulary from the point of ethnic and cultural enrichment of the language is so important.The article finds out the features of dialect use found in the novels of M. Dochynez: «Vichnyk», «Horyanyn» and «Krynychar» – significant for the present works, which are distinguished by the incredibly lively, rich language, which the author compares with the autumn bunch of grapes that blue sparkles in the sun.The article analyzes the dialectal features of M. Dochynez’ works primarily based on the vocabulary, because it reflects that conversational features of the author’s speech that give information about the material culture of the Transcarpathians (lexical and ethnographic dialecticisms), reproduce the character’s speech, reveal their view of the world, enhance the expressive possibilities of the language, stylistically underline and emotionally inspire the text. Key words: dialect vocabulary, works of M. Dochynez, lexical and ethnographic dialecticisms, specialty of the writer’s speech. References